Implementation of the Pendidikan Generasi Muda dan Kepramukaan (PGMK) for New Students as an Effort to Build the Spirit of State Defense Towards Advanced Indonesia - Irawan, Hendri; Hermawan, Dwi; Wijayanti, Tutik (Faculty of Social Science, Universitas Negeri Semarang, 2021)
The Scouting Young Generation Education or Pendidikan Generasi Muda dan Kepramukaan (PGMK) is an indoor and outdoor course conducted by new PPKn UNNES students. In practice, the subject is in the form of scouting education, which is held every Saturday. The implementation of PGMK activities is based on a scouting code of ethics. PGMK is an educational innovation in terms of strengthening character, especially concerning awareness and the spirit of defending the country. This study seeks to examine how the implementation of the Youth and Scouting Education practices; and the extent to which the Youth and Scouting Education practices are the spirit of defending the country in supporting the Advanced Indonesia Program. The research was conducted using a qualitative approach and the research location is in Semarang State University. The results showed that the Youth and Scouting Education is a compulsory subject education intended for new students. Apart from being held indoors, in practice, this education course is held every Saturday outdoors. In each activity, PGMK must be based on a scouting code of ethics. The PGMK curriculum contains highly relevant materials on the values of state defense for the younger generation. This research also formulates that the cultivation of values and characters of the spirit of state defense through Youth and Scouting Education is an actualization of the Nawa Cita program, namely policies that encourage and support advanced Indonesian programs.